Estudo da expressão dos genes TP53, VEGFA e HIF1α em pacientes com Síndrome Mielodisplásica, Citopenia Idiopática de Significado Indeterminado e Citopenias não Neoplásicas: associação com citocinas e fatores de prognóstico - Santos, Talyta Ellen de Jesus dos (2019)
Myelodysplastic Syndrome (MDS) is a complex set of diseases in which the diagnosis can be challenging, especially in patients who do not meet the criteria for MDS, but have unexplained cytopenias. The expression of genes involved in n eoplasias and the presence of substances in the medullary microenvironment may be relevant in the study of these conditions, since they interact directly with the healthy and neoplastic ce lls of the marrow. The aim of the study was to evaluate the expressi on of the TP53, HIF1 α and VEGFA genes and the cytokine levels VEGFA, IL 6, TNFα and IFN ᵧ in patients with MDS, Idiopathic Cytopenia of Indeterminate Significance (ICUS), Clonal Cytopenia of Undete rmined Significance (CCUS) and N on Neoplastic Cytopenias (C NN), associating the results with clinical, laboratory and prognostic factors. Initiall y, 85 patients were included. From these, 13 were excluded after confirming other diagnoses, remaining 72 participants: MDS (n = 34), ICUS (n = 31) and CNN (n = 7). Bone marrow samples were collected in EDTA to extract the genetic material and obtain the plasma. Gene e xpression was performed through the polymerase chain reac tion (PCR) in real time, with TaqMan ® system. Quantification of VEGF A, IL 6, TNFα and IFN ᵧ was performed by enzyme immunoassay (ELISA), according to the manufacturer's instructions. Epidemiological, clinical and laboratory data were taken from medical records. Statistical analysis was performed using GraphPadPrism5.0 and S PSS 24.1. The comparisons between the means of the groups were performed using Student's t test or Mann Whitney test or analysis of variance (ANOVA), depending on the n umber of groups. The overall survival curve was performed by the Kaplan Meier curve, thr ough the Cutt off finder program. Values of p <0.05 were considered significant. The mean age of patients with MDS, ICUS / CCUS and CNN was 74, 61 and 50, respectively. Blood count parameters were similar in the three groups, except for the monocyte coun t that was h igher in the MD S group (p <0.05 ). As for cytokines, IFN levels were similar between the SMD and ICUS / CCUS groups and decreased when compared to the CNN group (p = 0.017). The same was observed in relation to the expression of the HIF1 α gene, where the CNN group presented greater expression in relation to the others (p = 0.019). When analyzed according to cytopenias, VEGFA mRNA expression was higher in the group with h emoglobin levels between 8 10 g / dL (p= 0.038). Regarding platelets, TNFα lev els were higher in those with a count below 50,000 / mm³ (p= 0.01). Patients with medullary fibrosis presented higher levels of TNFα (p= and IL 6 (p= 0.001). In stratifying patients with MDS in early and advanced forms of the disease, a higher concentr ation of IFN ᵧ (p= was observed in the first group. However, for the cytokine TNFα, higher concentrations were obtained in the more advanced stage (p= 0.045). No associations were observed between the expression of the genes and the cytokines analyzed and the number of blasts and cytogenetics. The parameters evaluated did not influence the survival of patients in the study period. The results of the study allowed to conclude that the cytokine IFN ᵧ and the HIF1 α gene are more expressed in cyto penias of nonclonal origin and TNFα and IL 6 levels were associated with fibrosis. The results also suggested that the genes HIF1 α, VEGFA and TP53 act through mechanisms together, in view of the correlations obtained. New studies in this line of research will be us eful in elucidating the mechanisms involved in these processes of these different conditions.